Dietary Supplementation of Enzymatically Treated Artemisia annua L. Improves Lactation Performance, Alleviates Inflammatory Response of Sows Reared Under Heat Stress, and Promotes Gut Development in Preweaning Offspring - Xiong, Liang; Zhang, WenFei; Zhao, Hao; Tian, ZheZhe; Ren, Man; Chen, Fang; Guan, WuTai; Zhang, ShiHai (Frontiers in Veterinary Science, 2022)
Artemisia annua L., which known for its antimalarial compound artemisinin, has commonly used for its anti-inflammatory and anti-bacteria functions. Enzymatically treated Artemisia annua L. can improve its bioavailability. The purpose of this study was to investigate the effects of dietary supplementation of enzymatically treated Artemisia annua L. (EA) on lactation performance, serum hormone level, inflammatory factor, and immunity of heat-stressed sows. A total of 135 multiparous sows (Large White × Landrace) on d 85 of gestation were selected and randomly distributed into 3 groups with 45 replicates per group. The control group were reared under standard condition (temperature: 27.12 ± 0.18℃, THI (temperature-humidity index): 70.90 ± 0.80) and fed with basal diet. The heat stress (HS) and HS + EA groups, in which sows were raised in heat-stressed condition (temperature: 30.11 ± 0.16℃, THI: 72.70 ± 0.60) and fed with basal diets supplemented with 0 or 1.0 g/kg EA, respectively. This experiment was lasted for 50 consecutive days until d 21 of lactation. Compared with the control group, HS increased the concentrations of serum endotoxin and heat shock protein 70 (HSP-70), and the inflammatory cytokines in serum, colostrum and 14-d milk of sows. Meanwhile, it was found that the EA supplementation increased serum triiodothyronine (T3) level and average daily feed intake (ADFI) of heat-stressed sows during lactation, decreased levels of serum endotoxin, HSP-70 and inflammatory cytokines in sows and their offspring. The EA supplementation also decreased the inflammatory cytokines and somatic cell counts in colostrum of sows. In addition, the dietary supplementation with EA significantly increased the villus height in the duodenum and ileum of piglets. Collectively, EA supplement at 1.0 g/kg during late gestation and lactation increased ADFI in heat-stressed sows during lactation and enhanced average daily gain (ADG) of their offspring, this might due to the decreased endotoxin and inflammatory cytokines levels in serum and colostrum of heat-stressed sows, and the promoted gut development of piglets.